Experimental evidence for parasite-induced over-winter mortality in juvenile Rhodeus amarus - Michálková, V; Ondračková, M (Journal of fish biology, 2014)
In this study, the effects of the eye fluke Diplostomum pseudospathaceum (Trematoda) infection on over-winter survival of young-of-the-year (YOY) European bitterling Rhodeus amarus (Cyprinidae) were examined between September 2010 and April 2011. The fish were reared in semi-natural conditions to ensure that results were not confounded by other parasite infections. The cumulative mortality of R. amarus from November until April was significantly higher in D. pseudospathaceum-infected fish (57·3%) compared to controls (42·1%). Infection of the parental generation did not have any effect on the mortality of juveniles. The results indicate that D. pseudospathaceum infection increases over-winter mortality of YOY R. amarus. The possible mechanisms causing mortality are discussed.
Keywords: Fish Diseases; nemoci ryb; Diplostomum pseudospathaceum; bitterling; roční období; metacercariae; parasite infection; Seasons; Trematoda; Animals; Cyprinidae; zvířata